Alcohol, drugs and depressive symptoms in patients of psychiatric institutions in Maceió City, Alagoas State, Brazil (Research, Society and Development, 2020)
Objective: To identify symptoms of depression in users of alcohol and other drugs. Method: Study exploratory and descriptive, quantitative method. Performed in Portugal Ramalho Hospital and the Center for Attention to Alcohol and Other Drugs in Maceió-AL. It was used a social demographic questionnaire, Beck depression Inventory (BDI), Scale of the Montgomery-Asberg depression (MADRS), Hamilton Depression Scale (HAM-D). Applicated the Epi-Info version 3.5.3, statistical package SPSS, version 14.0.; chi-square and Fisher's exact test. Results: The sample consisted of 130 users. The profile was predominantly male, brown, unmarried, Catholic, low education level and social class. The drug most used was alcohol (CEAAD 60.0%, HEPR 53.0%). The initial use was between 10 to 20 years, the usage time up to 30 years. There were 63.3% participants with depressive symptoms by three scales. Conclusion: It was significant the presence of depressive symptoms in this population; no occurred, of systematized way, diagnosis for comorbidity.